A randomized clinical trial of three prompting systems to teach tact relations. Issue 2 (26th July 2019) - Cihon, Joseph H.; Ferguson, Julia L.; Leaf, Justin B.; Milne, Christine M.; Leaf, Ron; McEachin, John
Abstract : Prompts are commonly used during discrete trial teaching for individuals diagnosed with autism spectrum disorder (ASD). Three commonly used prompting systems include constant time delay, most‐to‐least prompting, and flexible prompt fading. Most of the research demonstrating the effectiveness of these three prompting strategies have been completed through the use of single subject experimental designs. Some within the field of behaviorally based approaches to ASD interventions have called for more randomized clinical trials of these approaches. The purpose of the present study was to compare these 3 prompting systems to teach tact relations for 27 individuals diagnosed with ASD through a randomized clinical trial without a control group with respect to pre–post responding, generalization, sessions to mastery, and responding during teaching. Overall, minimal differences were observed across the 3 systems. The results are discussed with respect to future research and clinical application of the methods evaluated.